CVD Synthesis of Hierarchical 3D MWCNT/Carbon-Fiber Nanostructures. (15th October 2008) - Susi, Toma; Nasibulin, Albert G.; Jiang, Hua; Kauppinen, Esko I.
Abstract : Multiwalled carbon nanotubes (MWCNTs) were synthesized by CVD on industrially manufactured highly crystalline vapor-grown carbon fibers (VGCFs). Two catalyst metals (Ni and Fe) and carbon precursor gases (C 2 H 2 and CO) were studied. The catalysts were deposited on the fibers by sputtering and experiments carried out in two different reactors. Samples were characterized by electron microscopy (SEM and TEM). Iron was completely inactive as catalyst with bothC 2 H 2 and CO for reasons discussed in the paper. The combination of Ni andC 2 H 2 was very active for secondary CNT synthesis, without any pretreatment of the fibers. The optimal temperature for CNT synthesis was750 ∘ C, with total gas flow of 650 cm 3 min − 1 ofC 2 H 2, H 2, and Ar in 1.0:6.7:30 ratio.